Zebularine Promotes Hepatic Differentiation of Rabbit Bone Marrow Mesenchymal Stem Cells by Interfering with p38 MAPK Signaling - Yong-Heng Luo; Juan Chen; En-Hua Xiao; Qiu-Yun Li; Yong-Mei Luo (Stem Cells International)
Demethylating agent zebularine is reported to be capable of inducing differentiation of stem cells by activation of methylated genes, though its function in hepatocyte differentiation is unclear. p38 signal pathway is involved in differentiation of hepatocytes and regulating of DNA methyltransferases 1 (DNMT1) expression. However, little is known about the impact of zebularine on bone marrow mesenchymal stem cells (BMMSCs) and p38 signaling during hepatic differentiation. The present study investigated the effects of zebularine on hepatic differentiation of rabbit BMMSCs, as well as the role of p38 on DNMT1 and hepatic differentiation, with the aim of developing a novel strategy for improving derivation of hepatocytes. BMMSCs were treated with zebularine at concentrations of 10, 20, 50, and 100 μM in the presence of hepatocyte growth factor; changes in the levels of hepatic-specific alpha-fetoprotein and albumin were detected and determined by RT-PCR, WB, and immunofluorescence staining. Expression of DNMT1 and phosphorylated p38 as well as urea production and ICG metabolism was also analyzed. Zebularine at concentrations of 10, 20, and 50 μM could not affect cell viability after 48 h. Zebularine treatment leads to an inhibition of DNMT activity and increase of hepatic-specific proteins alpha-fetoprotein and albumin in BMMSCs in vitro; zebularine addition also induced expression of urea production of and ICG metabolism. p38 signal was activated in BMMSCs simulated with HGF; inhibition of p38 facilitated the synthesis of DNMT1 and albumin in cells. Zebularine restrained DNMT1 and phosphorylated p38 which were induced by HGF. Therefore, this study demonstrated that treatment with zebularine exhibited terminal hepatic differentiation of BMMSCs in vitro in association with hepatocyte growth factor; p38 pathway at least partially participates in zebularine-induced hepatic differentiation of rabbit BMMSCs.